فعالية الواقع المعزز على التحصيل الدراسي لدى الطلبة في مادة العلوم في سلطنة عُمان - Al Balushi, Zulekha Ramadan Ali; Sahrir, Muhammad Sabri; Hussein, Suhailah (Academy of Scientific Research and Technology, Egypt, 2022)
This study aimed to discover the effect of teaching based on augmented reality technology on academic achievement in science for fourth grade students in the Sultanate of Oman. The study adopted a quasi-experimental approach to find out the effect of augmented reality on the educational process. The study sample consisted of 66 male and female students from two semesters from Al-Afiah Primary School; one of them, consisting of 33 students selected as a control group, while the other class, consisting of 33 students appointed as an experimental group. To achieve the objectives of the study, the researcher re-designed the third unit of the science textbook in the Sultanate of Oman using augmented reality technology, where the new science book designed using augmented reality (Ulum AR Book), based on the needs of the teacher and student to learn the science. The new science book (Ulum AR Book) taught to the students in the experimental group, while the students in the control group taught the same subject in the textbook in the traditional way. Two tests designed to measure academic achievement, a pre-, post- test. The validity and reliability of the academic achievement exams tested by Cronbach’s alpha coefficient, Couder-Richardson equation (21) and equivalence established between them. The validity and reliability of the student direction scale tested using Cronbach’s alpha coefficient. As for the analysis of the study data, it was done by using a two-way analysis of variance with repeated measures (Repeated Measures ANOVA). Results of the study showed a significant impact of the use of augmented reality technology on academic achievement. In addition, it also revealed the students’ perspectives, their desires, and their directions regarding the application of augmented reality technology in the educational process. The study was included with a set of recommendations.